Application of morphometric and stable isotope analyses for distinguishing domestic and wild geese. (6th January 2022) - Ehrlich, Freydis; Aguraiuja‐Lätti, Ülle; Lõugas, Lembi; Rannamäe, Eve
Abstract: Investigating the origins of goose domestication relies on successful identification of this species and, specifically, distinguishing it from its wild, morphologically similar, form. Here we present the first attempt to separate wild and domestic geese recovered from Estonian archaeological assemblages using a combination of morphometrics and stable isotope analysis. To this aim, measurements from 159 archaeological bones were compared with modern specimens. Twenty‐five archaeological samples were chosen for stable isotope analysis based on their morphometrics. The results of this paper show that bones identified as "domestic" by their size and shape had significantly higher δ 15 N values compared with those identified as "wild." The higher δ 15 N could be a result of dietary differences, for example, the role of manured crops and/or animal protein in the diets of domestic geese.